Adrenomedullin protects Leydig cells against lipopolysaccharide-induced oxidative stress and inflammatory reaction via MAPK/NF-κB signalling pathways - Hu, Wei (Sci Rep, 2017)
This study aimed to explore the possible benefits of adrenomedullin (ADM) in preventing oxidative stress and inflammation by using an in vitro primary culture model of rat Leydig cells exposed to lipopolysaccharide (LPS). Cell proliferation was detected through CCK-8 and BrdU incorporation assays. ROS were determined with a DCFDA kit, and cytokine concentrations were measured with ELISA assay kits. Protein production was examined by immunohistochemical staining and Western blot, and gene expression was observed through RT-qPCR. Results revealed that ADM significantly reduced LPS-induced cytotoxicity, and pretreatment with ADM significantly suppressed ROS overproduction and decreased 4-HNE and 8-OHdG expression levels and concentrations. ADM pretreatment also significantly attenuated the overactivation of enzymatic antioxidants, namely, superoxide dismutase, catalase, thioredoxin reductase, glutathione peroxidase, glutathione reductase and glutathione-S-transferase. ADM supplementation reversed the significantly increased gene expression levels and concentrations of TNF-α, IL-1β, TGF-β1, MCP-1 and MIF. ADM pretreatment significantly inhibited the gene expression and protein production of TLR-2 and 4. Furthermore, ADM pretreatment markedly reduced the phosphorylation of JNK, ERK 1/2 and p38, phosphorylation and degradation of IκBα and nuclear translocation of p65. Our findings demonstrated that ADM protects Leydig cells from LPS-induced oxidative stress and inflammation, which might be associated with MAPK/NF-κB signalling pathways.